Integration of Digital Technology in Mathematics Learning: A Review of the Literature on Pedagogical and Cognitive Impacts - Lalu Aji Muliardi Akbar; Qiara Azahra (Gema Cendekia Institute, 2026)
The integration of digital technology in mathematics learning is a strategic issue in line with the demands of strengthening high-level thinking skills and transforming education in the digital era. This study aims to comprehensively analyze the pedagogical and cognitive impact of the integration of digital technology in mathematics learning based on the latest empirical findings. The method used is a systematic literature review of peer-reviewed articles published in the period 2020–2025 and indexed in reputable databases, such as Scopus, Web of Science, ERIC, and Google Scholar. The analysis is carried out through narrative and thematic synthesis by grouping the findings into pedagogical and cognitive dimensions. The results of the study show that the integration of digital technologies, including visualization devices, interactive media, and artificial intelligence, contributes positively to improving the quality of mathematics learning, especially in terms of cognitive engagement, conceptual understanding, and the development of mathematical reasoning. However, the effectiveness of technology integration is highly dependent on pedagogical design, teachers' digital pedagogical competencies, and institutional support. In conclusion, digital technology is not deterministic, but functions optimally as a pedagogical instrument when consciously cognizant and contextual are integrated. This study makes a theoretical and practical contribution to the development of meaningful and sustainable technology-based mathematics learning.